Panama : 2016 article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Panama. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights Panama's expected continued growth-among the strongest in Latin America-against a backdrop of low inflation, a stable financial system, and a declining current account deficit. GDP grew by 5.8 percent in 2015, and growth is projected to remain at about 6 percent in 2016 and over the medium term. The economy will be supported by the expected opening of the expanded canal and lower fuel prices. The overall fiscal deficit is expected to consolidate to 1.2 percent of GDP over the medium term. Public debt is projected as sustainable.